Strategic Planning of Striped Catfish (Pangasianodon hypophthalmus) Farming in East Tanjung Jabung Regency, Jambi Province - Asro Nurhabib; Diana Arfiati; Aida Sartimbul (Indonesian Journal of Environment and Sustainable Development, 2017)
East Tanjung Jabung regency is a district that has a fairly large fisheries potential, but the existing potential has not been utilized maximally. The absence of a policy strategy leads to the problem of undeveloped striped catfish farming in this region. This study is amid to formulate the policy strategies of iridescent striped catfish farming.  This study was conducted from July to September 2016 in East Tanjung Jabung Regency, Jambi Province. This study employed both descriptive qualitative and quantitative method followed by SWOT analysis which was used to determine the strengths, weaknesses, opportunities and threats of striped catfish farming. The results of SWOT analysis suggest some policy strategies to improve the striped catfish farming. First, prevent the increase of water level in the rainy season. Second, anticipate the acidity of water in the peat area. Third, increase human resources quality in economic field. Fourth, improve supervision and surveillance of the farming area. The last, develop the use of natural food.Keywords: Strategic Planning; Striped Catfish Farming; SWOT analysis